Analysis of the Taxonomy, Synteny, and Virulence Factors for Soft Rot Pathogen Pectobacterium aroidearum in Amorphophallus konjac Using Comparative Genomics - Zhang, Yanan; Chu, Honglong; Yu, Liqiong; He, Fei; Gao, Yong; Tang, Lizhou (Frontiers in Microbiology, 2022)
Bacterial soft rot is a devastating disease for a wide range of crops, vegetables and ornamental plants including Amorphophallus konjac. However, the pangenome and genome plasticity of the konjac soft rot pathogens is little explored. Here, 11 candidate bacterial isolates were proven to cause typical soft rot symptoms in konjac by in vitro and in vivo pathogenicity tests, and further used for whole genome sequencing. Based on in silico DNA–DNA hybridization, average nucleotide identity and whole-genome SNP phylogeny, all these isolates were determined to be Pectobacterium aroidearum. In addition, synteny analysis of these genomes revealed considerable chromosome inversions, one of which is triggered by homologous recombination of ribose operon. Pangenome analysis and functional enrichment showed that the pangenome of P. aroidearum is open and the accessory genes are enriched in a COG category for replication, recombination and repair. Variations in bacterial secretion systems especially for type IV secretion system are found while plant cell wall degrading enzymes are conserved. Furthermore, sequence analyses also provide evidence for the presence of type V secretion system in genus Pectobacterium. To sum up, these findings advance our understanding of the pathogenicity determinants, genome plasticity and evolution of P. aroidearum.